Role of duplex ultrasonography in patients with renal parenchymal disease: renal resistive index vs serum creatinine level - Shiekh, Yassar; Khan, Aamir Javed; Bhawani, Shafqat Shabir (International Journal of Advances in Medicine, 2019)
Background: In view of the fact that Brightness (B)-mode ultrasound findings in patients with renal parenchymal disease are profoundly non-specific, this study was carried out to determine the efficiency of color Doppler sonography for assessing renal function. In this series, the relationship between the resistive index (RI) of renal interlobar artery and serum creatinine level was analyzed for any relevant association of this color Doppler index with the serum creatinine level. Methods: In this prospective cross-sectional study, 40 patients with renal parenchymal disease having serum creatinine level >1.4 mg/dL were chosen midst routine revisits. The control group comprised of 40 normal subjects with serum creatinine levels <1.4 mg/dL. After assessing the kidneys of these subjects with gray-scale ultrasound for presence of any stones, hydronephrosis, and/or space occupying lesions instead of, they were subsequently interrogated with color Doppler sonography and RI calculated. Results: The mean serum creatinine levels±SD in the case and control groups were 6.7±0.7 mg/dL and 1.0±0.4 mg/dL, respectively. The mean±SD resistive index (RI) was 79.0%±1.8% in the diseased group and 60.3%±0.7% in the healthy subjects (p<0.001). The correlation between the RI and the serum creatinine level was statistically significant (p<0.001). Conclusions: Resistive index (RI) measurement by color doppler ultrasonography is a reasonable prognosticator of functional outcome in patients with renal parenchymal disease.